Sociodemographic factors associated with depression in students of a public high school in the state of Querétaro, Mexico - Hernández Rodríguez, Verónica Margarita (2022)
Objective: To determine the sociodemographic factors associated with depression in students of a public high school in the state of Querétaro, Mexico. Method: Quantitative research, descriptive-correlational scope and cross section. Sample made up of 418 students. Collection of information through a sociodemographic data card and Beck Depression Inventory-IA (BDI-IA). Analysis by descriptive statistics in the SPSS program, while the inferential statistics were performed in the R software through Pearson's Chi square from a contingency table for the level of depression and each sociodemographic factor. Consent and informed assent were provided, respecting at all times the confidentiality, freedom and will in the participation of adolescents. Main results: 57.7% women, 49% were enrolled in the first year, 62.4% attended class in the morning shift, 91.9% dedicated themselves only to study and 58.1% practiced sports. 16% have mild mood disturbance, 5.3% intermittent depression, 4.3% moderate, 1.9% severe and 1% extreme depression. In the correlation between sex and level of depression, X2=33.833 (p=8.062e-07), school grade and level of depression were obtained X2=21.288 (p=0.006421), sports practice and level of depression X2=13.195 (p=0.01036), shift and level of depression X2=5.5836 (p=0.2325), occupation and level of depression X2=6.1243 (p=0.1901), level of depression and with whom does the adolescent lives X2=20.372 (p=0.06037). Overall conclusion: Sociodemographic factors such as gender, school grade and sports practice are directly associated with levels of depression in adolescents. The shift, occupation and with whom he lives are factors that are not related to the presence of depression.